ANALYSIS OF DVB-T2 USAGE IN MONGOLIAN DIGITAL TELEVISION BROADCASTING - Bayarmunkh Bulten, (International Journal of Innovative Technologies in Social Science, 2025)
In today's rapidly advancing world of information technology, the ability of television networks to transmit important information quickly and reliably is increasingly critical. Enhancements in broadcasting systems, such as the adoption of digital technology, have led to improved data storage and better quality of service (QoS). Modern transmission technologies, including the DVB-T2 digital television broadcasting system, have become widely implemented. This research examines the Mongolian DVB-T2 digital television system, analyzes common issues with DVB-T2 receivers (set-top boxes), and provides recommendations for their effective usage.